Manejo agronómico del cultivo de mamey colorado (Pouteria sapota) - Villegas Chora, Germán Benigno (2021)
This research details the agronomic management of the cultivation of red mamey (Pouteria sapota), the fruit of the mamey sapote tree is consumed fresh and is highly appreciated for its organoleptic characteristics, in our country farmers do not grow it because they do not consider it as a profitable crop. Among the conclusions, it is determined that the seed is used in a medicinal, cosmetic and nutritional way as semisolid petroleum jelly, soaps and pharmaceutical products. In addition, the seed is administered orally to counteract kidney diseases and as an antirheumatic, the latex produced by the tree has anthelmintic and emetic properties, and in some places it is used to remove warts and fungi from the skin.